Online Monitoring Water Level in Rainwater Harvesting (RWH) Storage Tank - Rahmat, Siti Nazahiyah; Md Tomari, Mohd Razali; Mohammad Harmay, Nurul Syahira; Ahmad Tarmizi, ‘Aainaa Hatin (Penerbit UTHM, 2020)
Rainwater harvesting (RWH) system has gained recognition as one of the sustainable means to manage a water crisis in the future. Due to the increase of global population demand, problems related to the water scarcity slowly become a serious issue in Malaysia as well as other countries. The implementation of RWH system aims to supply adequate water resources to consumers with a significant reduction of costs. The significant economic savings of RWH is related to the rainwater tank capacity. Typically, the size of the rainwater harvesting system is determined based on the size of the roof catchment area and the rainfall data from the existing rain gauge. However, a problem arises when sometimes the dependency of design analysis on monthly rainfall data are likely to overestimate the sizing of water tank recommended for daily use. In this study, the integration between the RWH system and automatic water level detection was done to improve the current system of RWH. Water level detection system was installed in the rainwater storage tank to detect and monitor water level; hence, it will help to estimate the available water in the rainwater storage tank and to avoid any overdesign problems. The results showed that the automatic water level detection system operated efficiently during the one month with hourly output data.